Estudo biológico e biométrico dos estádios ninfais de Rhodnius prolixus Stäl, 1859 (Hemiptera, Reduviidae) sob condições laboratoriais - Marconato, E. [UNESP]; Ponsoni, E. J. [UNESP]; Barata, J. M S; Da Rosa, João Aristeu [UNESP] (My University, 2006)
Eggs and nymphs originated from couples of Rhodnius prolixus obtained from nymphs of the 5th instar were used for biological cycle and biometric studies. The following biological cycle parameters were determined under a temperature of 28°C and relative humidity, varying between 52 - 94% : medium period of incubation: 13.01 days; rate of eggs eclosion: 77.6%; medium period of development of the 1st, 2nd, 3rd, 4 th, 5th instar nymphs : 19.33, 19.09, 20.38, 24.37, 38.14 days, respectively; percentual of deaths in the nymph instar: 26.70, 14.00, 18.26, 17.02, 35.47% respectively; percentual of changes per instar nymphs; 73.30, 86.03, 81.73, 82.97, 64.52%, respectively. Biometric measurements performed, showed that in all the instars the abdomen is the largest segment. In the four first instars, the head is larger than the thorax. In the fifth instar, the head and thorax present are about the same size.

A partir de ninfas de 5o estádio obtiveram-se casais de Rhodnius prolixus, que originaram ovos e ninfas para estudos de ciclo biológico e biométrico. Foram determinados os seguintes parâmetros do ciclo biológico à temperatura de 28OC e umidade relativa do ar variando entre 52 e 94%: período médio de incubação dos ovos: 13,01 dias; taxa de eclosão dos ovos: 77,6%; período médio de desenvolvimento do 1º, 2º, 3º, 4º e 5º estádio ninfal: 19, 33; 19,09; 20,38; 24,37; 38,14 dias, respectivamente; percentual de mortes nos estádios ninfais: 26,70; 14,00; 18,26; 17,02; 35,47% respectivamente; percentual de mudas por estádio ninfal; 73,30; 86,03; 81,73; 82,97 e 64,52%, respectivamente. Estudo biométrico mostrou que o abdômen é o maior segmento em todos os estádios. Nos quatro primeiros estádios a cabeça apresenta-se maior que o tórax, enquanto no quinto estádio a cabeça e o tórax apresentam portes equivalentes.
Biological and biometric studies of the nymph instars of R. prolixus (Hemiptera, Reduviidae)
Keywords: Biometrics; Life cycle; Rhodnius prolixus; abdomen; analytical parameters; biology; biometry; death; developmental stage; egg; head; Hemiptera; humidity; incubation time; life cycle; nonhuman; nymph; Rhodnius; rhodnius prolixus; temperature; thorax